ANALISIS BENTUK DAN FUNGSI EUFEMISME DALAM BAHASA TABU PADA SINIAR “ORMAS” DEDDY CORBUZIER - Endang Sholihatin; Muhammad Arik Sunanul Huda; Syahrul Permana Putra; Akhmad Azrul Arsyadhany; Muhammad Faris Syaifulloh; Muhammad Rizqi Amanan Habibulloh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to explain the form and function of euphemisms in Deddy Corbuzier's "ORMAS" podcast using a qualitative approach. The main data source is Deddy Corbuzier's "Ormas" broadcast in October 2023, and the data collection technique involves Listen Free to Engage Cakap (SBLC), Recording Technique, and Note-Taking Technique. SBLC, as the main method, allows researchers to be observers without being involved in the conversation, focusing on linguistic events outside themselves. The recording technique is used to record the data obtained, while the recording technique is carried out after applying the first and second techniques. Data analysis was carried out simultaneously with data collection, following the Miles and Huberman analysis model (1992: 23), which involves the steps of data collection, data reduction, data presentation, and drawing conclusions. This research succeeded in identifying 19 euphemism data in Deddy Corbuzier's "Ormas" Siniar in October. The form of euphemism in this podcast involves abbreviations, loan words, foreign terms and metaphors. The function of euphemisms is divided into three categories, namely softening speech, diplomacy, and keeping something secret.